Economic Studies and Its Activities in Islamic Religion Point of View - Syihabudin, . (Modern Perspectives in Economics, Business and Management Vol. 1, 2021)
Economic activities in the view of Islam are suggestions and demands of life that have a religious dimension. If viewed solely from the goal, there is no difference between the Islamic economic system and other economic systems. This is because all economic systems, including the Islamic economic system in it, work for the same goal, namely fulfillment of various needs of life, both personally and society as a whole. In Islamic economics, this material gain is merely an intermediary for a greater goal and a higher ideal, namely the prosperity of the earth and prepares it for human life. In general, Islamic economics aims to prosper the earth and improve the standard of human life that is decent, just and balanced between self-interest and other people, between material and spiritual, and between rights and obligations. Apart from the above objectives, Islamic economics with the instruments of zakat, infaq, alms, grants and waqf, with productive management, aims to eradicate poverty which is not absolute.